Teoria integracji pojęciowej jako narzędzie badania twórczości Joanny Bator - Siniarska-Tuszyńska, Angelika (Zagadnienia Rodzajów Literackich, 2019)
The theory of conceptual integration / blending is a methodology that enables decoding of complex semantic structures. It not only allows to correctly read hidden meanings of polysemantic concepts, but also to analyse how these structures were created. The concept of blending is useful not only for researchers (especially in the interpretation of numerous cultural texts), but also for authors at the stage of creating their works. An appropriate process of blending guarantees the creation of new, original qualities resulting from a combination of several conceptual structures into one and it also enables the expression of ideas difficult to articulate. The examples of such multidimensional concepts can be found in the novels of Joanna Bator (the laureate of Nike Award in 2013), who (being a cultural expert and anthropologist) tackles in her works various philosophical or sociological issues. She presents her critical observations as specific — metaphorical, metonymic, symbolic and blended — images. This article provides several such examples in order to present how creating and reading blends is connected with “watching” and creative writing as well as sensual and rational exploration of things/meanings in culture.